Parallel computing technologies : 15th International Conference, PaCT 2019, Almaty, Kazakhstan, August 19-23, 2019 : proceedings /: 15th International Conference, PaCT 2019, Almaty, Kazakhstan, August 19-23, 2019 : proceedings. ([2019]) - Unknown
No abstract available